No pass no drive: Education and allocation of time - Rashmi Barua; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2012)
Do negative incentives or sticks in education improve student outcomes? Since the late 1980s, several U.S. states have introduced No Pass No Drive (NPND) laws that set minimum academic requirements for teenagers to obtain driving licenses. Using data from the American Community Survey (ACS) and Monitoring the Future (MTF), we exploit variation across state, time, and cohort to show that NPND laws led to a 6.4 percentage point increase in the probability of graduating from high school among black males. Further, we show that NPND laws were effective in reducing truancy and increased time allocated to school-work at the expense of leisure and work.
urn:nbn:de:101:1-201208065460
Keywords: J08; J22; I2; 330; negative incentives; education; allocation of time; dropout; No Pass No Drive laws; Bildungsabschluss; Verkehrsverhalten; Zeitverwendung; Abbrecher; USA